Partnering with suppliers for quality improvement - Baliso, Unathi (Cape Peninsula University of Technology, 2010)
Uneven surfaces on national roads that often lead to difficulty and even danger can be extremely hazardous when wet, due to mud and cracks, and also create dust pollution for motorists, pedestrians, residents and business. The continuing use of low quality raw materials in producing hot mix asphalt for national roads, leads to regular maintenance at a very high cost. The quality aggregates (stone that is used to produce asphalt), and the quality of bitumen are often inadequate for the correct composition of hot mix asphalt. The mst important factors affecting initial and long term performance of the highways is the inferior pavement structure and condition, due to poor aggregates (raw material)from suppliers. The performance of asphalt i s largely determined by the characteristics of its constituents, the asphalt binder and aggregates.
Thesis (MTech (Quality))--Cape Peninsula University of Technology, 2010
Keywords: Roads -- South Africa -- Design and construction; Aggregates (Building materials) -- South Africa. -- Quality control; Total quality control; Total quality management -- South Africa